PENGEMBANGAN MEDIA PEMBELAJARAN MENULIS TEKS NEGOSIASI BERBASIS APLIKASI PREZI PADA SISWA KELAS X SMA - Anna Wijayanti (LOA: Jurnal Ketatabahasaan dan Kesusastraan, 2019)
This study aims to describe the design development, the implementation, and the feasibility of learning media of text writing based on prezi negotiation on grade X of senior high school students. It uses research and development method. The development of this learning media is elaborated in accordance with the development stage of the procedural model based on Borg and Gall. This development research model is conducted only until step seven, that are (1) need analysis, (2) product design and development,(3) product validation I, (4) small group test, (5) product validation II, (6) large group test, and (7) evaluation and dissemination. The pre test and post test reveal that the learning outcome is 34.4% higher after using the media. Thus, it can be concluded that the learning media is feasible to be applied in learning process.